Near-Infrared Imaging Using Intravenous Indocyanine Green at a Conventional Dose to Locate Pulmonary Metastases: A Pilot Study - Hamaji, Masatsugu; Chen-Yoshikawa, Toyofumi Fengshi; Minami, Manabu; Date, Hiroshi (The Thoracic and Cardiovascular Surgeon, 2019)
Intravenous indocyanine green (ICG) has been reported to localize intra-abdominal metastatic lesions in several clinical trials. Our pilot study aimed to investigate the feasibility and safety of ICG fluorescence localization in pulmonary metastasectomy using a near-infrared fluorescence thoracoscope. Each patient received intravenous 0.25 or 0.5 mg/kg of ICG. The maximum diameter of the tumor on computed tomography ranged from 0.5 to 3.5 (median: 1.15) cm. Intravenous ICG injection localized pulmonary metastases in a portion (3 patients) of the enrolled patients. Our preliminary results provided us with important information to modify the study protocol.
Keywords: pulmonary metastasis; clinical trial; near-infrared